Colonial and Post-Colonial Governance of Islam Continuities and Ruptures - Bader, Veit; Maussen, Marcel; Moors, Annelies (Amsterdam University Press, 2011)
The contributors analyse the mutual impact of colonial and postcolonial governance on the development, organisation and mobilisation of Islam paying special attention to the ongoing battles over the codification of Islamic education, religious authority, law and practice while outlining the similarities and differences, the continuities and ruptures in British, French and Portuguese colonial rule in Islamic regions. Using a shared conceptual framework they examine the nature of regulation and its outcomes in different historical periods in selected African, Middle Eastern, Asian and European countries. This authoritative study opens up new vistas for research in Islamic studies.